The Implementation of Class Action As a Legal Effort for Mass Poisoning Victims in the Free Nutritional Meal Program - Rheyna Wisnu Puteri; Kaharuddin Kaharuddin (Eduvest - Journal of Universal Studies, 2026)
The Free Nutritious Meal (Makan Bergizi Gratis or MBG) program, launched in early 2025 to combat malnutrition in Indonesia, has been marred by mass food poisoning affecting thousands of students due to bacterial contamination. This research examines negligence within the MBG management and the application of class action mechanisms as legal protection for victims. Using a normative legal method with a statutory approach, the study analyzes the Consumer Protection Law, the Indonesian Civil Code, and Supreme Court Regulation No. 1/2002. Findings indicate that beneficiaries hold legal standing as "end consumers," establishing a clear basis for legal accountability. A class action is identified as the most proportional instrument for efficiently seeking both material and immaterial damages in mass tort cases. This study contributes to existing legal scholarship by demonstrating how class action mechanisms can address contemporary public health crises within Indonesia's consumer protection framework, particularly in government-sponsored nutrition programs where traditional individual litigation proves inefficient and economically prohibitive for vulnerable populations. Implicatively, this mechanism serves as a behavior modification tool for managers (BGN Partners) to improve food safety standards through legal deterrence. The government must immediately enact written regulations to provide a solid legal foundation for the implementation of the MBG program. Strengthening this regulatory framework is crucial to ensuring legal certainty, clarifying management accountability mechanisms, and guaranteeing policy transparency.